Analysis of the suspected cancer‐causing potassium bromate additive in bread samples available on the market in and around Dhaka City in Bangladesh. Issue 7 (24th May 2021) - Mahmud, Syed Sadman; Moni, Mukta; Imran, Abu Bin; Foyez, Tahmina
Abstract: Bread is one of the most popular foods consumed worldwide. It is a very popular foodstuff consumed in almost every house in Bangladesh as breakfast. Bread is prepared predominantly from flour to meet the daily carbohydrate demand and enhances its overall nutrition value using various ingredients. Potassium bromate (KBrO3 ) is an alluring additive to improve bread quality by bread makers. But due to the well‐known toxic and carcinogenic effect, certain levels of KBrO3 residue are not suitable for bread, and it is therefore forbidden in many countries. The key objective of this study is to evaluate the safety status of bread in Dhaka City and its proximity to Bangladesh. Twenty‐one randomly collected bread samples were tested in this study from different bakeries or shops in and around Dhaka City. The levels of KBrO3 were analyzed spectrophotometrically, and the maximum concentration found in the bread sample was 9.29 μg/g. A total of 67% of collected bread samples showed elevated levels of KBrO3 relative to the allowable amount prescribed by various Food and Drug Administration worldwide. KBrO3 is toxic to consumers and could endanger their health over continuous regular consumption and thus need to be monitored strictly. Abstract : A total of twenty one randomly collected bread samples were tested in this study from different bakeries or shops in and around Dhaka city. The levels of KBrO3 were analyzed spectrophotometrically and the maximum concentration found in the bread sample 9.29 μg/g. A total of 67% of samples showed elevated levels of potassium bromate, which is extremely toxic to consumers and could endanger their health over continuous regular consumption thus need to be strictly monitored.